Regulation of Formation, Stemness and Therapeutic Resistance of Cancer Stem Cells - Jing, Nan; Gao, Wei-Qiang; Fang, Yu-Xiang (Frontiers in Cell and Developmental Biology, 2021)
Over the past 20 years cancer stem cells (CSCs) have been proposed as key players in the tumorigenesis and progression, which are closely related to the initiation, metastasis and therapeutic resistance of cancer. Evidences have been provided that both genetic and epigenetic factors contribute to the regulation of the formation and stemness maintenance as well as the therapeutic resistance of CSCs via affecting various signal pathways. In addition, the interaction between CSCs and tumor microenvironment has also been revealed to be involved in the above-described processes. With the aim of targeting CSCs to improve treatment outcome, we herein discuss the mechanisms that orchestrate the characteristic of CSCs by the three elements and potential therapeutic strategies. We also summarize how several key regulatory factors function in the regulation of not only the formation and stemness maintenance, but also the therapeutic resistance of CSCs. Thus, future studies focusing on these key factors would be helpful for the development of novel drugs targeting CSCs.